Vibrational Spectra, Crystal Structures, Constitutional and Rotational Isomerism of FC(O)SCN and FC(O)NCS - Ramos, Luis A. (2010)
Fluorocarbonyl thio- and isothiocyanate, FC(O)SCN and FC(O)NCS, were fully characterized by IR (gas, Ar and N2 matrixes), Raman (liquid and solid), UV (gas), and 13C NMR (liquid) spectroscopy, as well as single-crystal X-ray diffraction. Their vibrational and conformational properties were analyzed using matrix isolation techniques guided by quantum chemical calculation at the ab initio [MP2 and CCSD(T)], density functional theory B3LYP, and CBS-QB3 levels of theory. A complete assignment of the fundamental modes of FC(O)SCN was performed. In both the gas and liquid states, FC(O)SCN and FC(O)NCS were found to exist as two conformers (Cs symmetry), in which the carbonyl double bond (C═O) adopts a synperiplanar (syn) and an antiperiplanar (anti) orientation with respect to either the SCN or NCS group. For FC(O)SCN, the conformational enthalpy difference, ΔH° = H°(anti) − H°(syn), was determined by matrix IR experiments to be 0.9 ± 0.2 kcal mol−1. The conformational equilibria were evaluated by fast-cooling gaseous samples highly diluted in argon at different temperatures as cryogenic matrixes. The conformational properties of both molecules were analyzed in terms of the hyperconjugative electronic effect applying the natural bond orbital method. The kinetics of the thermal conversion of the high-energy anti into the syn FC(O)NCS conformer was studied in Ar and N2 matrixes at cryogenic temperatures. The reversed syn → anti photoisomerization was observed using UV−vis light. Rearrangement of FC(O)SCN into FC(O)NCS was observed in the neat liquid and in solution. Under 193 nm (ArF excimer laser) irradiation, FC(O)NCS isolated in cryogenic Ar matrixes forms FC(O)SCN. At low temperature, single crystals of the two constitutional isomers were obtained using a miniature zone melting procedure. According to X-ray diffraction, they exclusively crystallize in their syn forms (Cs symmetry) in the orthorhombic crystal system.